2022
DOI: 10.24191/mjssr.v18i1.17641
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Taking Part in Physical Activites Based on Gender

Abstract: There are many reasons why individuals participate in sports or physical activities. There are two main types of motives for engaging in physical activities, which is intrinsic and extrinsic motivation. Previous research found that the six important motives, given by student-athletes for sport participation, were achievement, body shape, physical fitness, teamwork, learning new skills and challenges. However, research comparing the difference on motives for taking part in physical activities, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Similar to these results, a study by Molanorouzi et al [ 38 ] conducted among adults from Malaysia, shows that males have a higher motivation for mastery and competition/ego, whereas females have a higher motivation for appearance and physical condition [ 38 ]. In contrast with our results, the research from Malaysia suggested that there are no significance differences in the motives for taking part in PA, between the genders, among student-athletes [ 39 ]. Vanlalduhsaki et al [ 34 ] show that there is a statistically significant higher intrinsic and identified motives for male medical students, compared to female medical students, from India.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to these results, a study by Molanorouzi et al [ 38 ] conducted among adults from Malaysia, shows that males have a higher motivation for mastery and competition/ego, whereas females have a higher motivation for appearance and physical condition [ 38 ]. In contrast with our results, the research from Malaysia suggested that there are no significance differences in the motives for taking part in PA, between the genders, among student-athletes [ 39 ]. Vanlalduhsaki et al [ 34 ] show that there is a statistically significant higher intrinsic and identified motives for male medical students, compared to female medical students, from India.…”
Section: Discussioncontrasting
confidence: 99%